International trade and the environment: theoretical and policy linkages - Neary, J (Springer, 2006)
I review and extend three approaches to trade and environmental policies: competitive general equilibrium, oligopoly and monopolistic competition. The first two have surprisingly similar implications: deviations from first-best rules are justified only by constraints on policy choice (which motivates what I call a “single dividend” approach to environmental policy), and taxes and emissions standards differ in ways which reflect the Le Chatelier principle. I also show how environmental taxes may lead to a catastrophic relocation of industry in the presence of agglomeration effects, although not necessarily if there is a continuum of industries which differ in pollution intensity.